Diary of a wimpy kid : the last straw - Kinney, Jeff.; Amulet Books (London : Puffin Books, 2009)
Middle-schooler Greg Heffley nimbly sidesteps his father's attempts to change Greg's wimpy ways until his father threatens to send him to military school.
6.1
5-8
Keywords: Families -- Juvenile fiction; Middle schools -- Juvenile fiction; Schools -- Juvenile fiction; Diaries -- Fiction; Family life -- Fiction; Humorous stories; Middle schools -- Fiction; Schools -- Fiction; Humorous fiction; School stories